TEKNIK DAN METODE PENERJEMAHAN LIRIK LAGU AKB48 KE JKT48 - Azmy, Rizhal (Humanis; Volume 12. No.3. September 2015, 2015)
The title of this research is “ The Translation Technique and Method of song lyrics translation from AKB048 to JKT48 ” This research describe the translation technique and method which applied on translating AKB48 to JKT48’s song lyrics . The theoriesused in this research aretranslation technique according to Molina and Albir (2002) and translation method according toNewmark (1998). The data resources are 3 songs of AKB48 and JKT48 wich is name are Heavy Rotation , Koisuru Fortune Cookie, and RIVER. The data were analyzed with ditributive method and technique of direct decisive element. The results of this research show that from 89 translation unit/, 52 datas (58,43%) are literal translation technique, 12 datas (13,48%) are borrowing technique, 8 datas (8.99%) are astablished equivalent, 11 datas (12,36%) are aplification technique, 5 datas (5,62%) are modilation technique, and 1 data (1,12%) is transposition technique. While the orientation of the translation method is the source  language.
Keywords: song lyrics translation, translation technique, translation method